Reinterpreting Mother Earth: Translation, Governmateriality, and Confidence - Tafjord, Bjørn Ola (Journal for the Study of Religion, Nature and Culture, 2024)
The author responds to Gill’s interpretation of Mother Earth as a name, a meme, and a conspiracy and argues it can become more compelling and perhaps less confrontational if it is supplemented with an alternative set of analytical terms. To tweak the perspective and the tone a bit, suggesting we try ‘translation’, ‘govern-materiality’, and ‘confidence’.